The Concept and Application of Anti Suit Injunction in Civil Proceedings of European Union Member States and Lithuania - Doržinkevič, Artur (Teisė, 2022)
This article analyzes the concept, origins and application of anti suit injunction. The author examines possibilities of applying anti suit injunction in the case law of the Court of Justice of the European Union and in the case law of individual Member States – Germany and France. After evaluating the examples of foreign court practice, a legal assessment of a possibility to apply anti suit injunction in Lithuanian court practice is presented.
Keywords: anti suit injunction; international civil procedure; jurisdiction; competence of courts